Edukasi Pemberian Makanan Pendamping ASI yang Tepat dalam rangka Pencegahan Stunting dengan Melibatkan Tokoh Masyarakat - Elwitri Silvia; Endang Sari; Welly Handayani; Mekar Zenni Radhia; Hanifa Zaini (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Stunting is still a problem for health status of children in Indoensia which has an impact on children’s cognitive development and it is irreversible and has an intergenerational impact so that the productivity levelof Indonesia’s next generation is predicted to be still half of its potential. Stunting is related to nutritional intake in the first 1000 days of life associated with cimplementary feeding. The period of complementary feeding is an important opportunity to prevent all forms of childhood malnutrition including stunting. Education about complementary feeding is one of the steps in reducing stunting. The purpose of this activity is to provide education on the provision of appropriate complementary foods to prevent stunting by involving community leaders at the Nagari Tanah Datar 10 Koto Hall, Padang Panjang. This activity was attended by wali nagari, babinsa and bhabinkantibmas. Participants in the activity are family members (parents) who have children aged 6-24 months. The activity was attended by 28 people. This activity is carried out simultaneously with the distribution of direct cash assistance. The implementation method in this health education activity uses lecture method, discussion, question and answer method. Media used are LCD projectors and leaflets. Before the education started, each participant was given a leaflet. The educational activities were divided into two sessions. The first session was the delivery of material and the second session was a discussion and question and answer session with the participants. The activity went smoothly, participants actively participated during the activity.